2008
DOI: 10.1016/j.psychsport.2007.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism and performance in a new basketball training task: Does striving for perfection enhance or undermine performance?

Abstract: Objectives: In the psychology of sport and exercise, the question of how perfectionism affects performance is highly debated. While some researchers have identified perfectionism as a hallmark quality of elite athletes, others see perfectionism as a maladaptive characteristic that undermines, rather than helps athletic performance. Against this background, the purpose of the present study was to investigate how different aspects of perfectionism predict performance and performance increments.Method: A study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
48
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 38 publications
5
48
1
1
Order By: Relevance
“…Whereas three of the four studies found perfectionistic strivings to predict higher performance (Stoeber, Uphill, & Hotham, 2009, Studies 1 and 2;Stoll, Lau, & Stoeber, 2008), one study found perfectionistic strivings to predict lower performance after failure (Anshel & Mansouri, 2005) and one study found that athletes high in perfectionistic strivings and high in perfectionistic concerns-J. Stoeber: Perfectionism and Performance 12 that is, athletes who would be considered "unhealthy" perfectionists according to the model in Figure 1-showed the largest performance increments over a series of trials .…”
Section: Sport Performance [H2]mentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas three of the four studies found perfectionistic strivings to predict higher performance (Stoeber, Uphill, & Hotham, 2009, Studies 1 and 2;Stoll, Lau, & Stoeber, 2008), one study found perfectionistic strivings to predict lower performance after failure (Anshel & Mansouri, 2005) and one study found that athletes high in perfectionistic strivings and high in perfectionistic concerns-J. Stoeber: Perfectionism and Performance 12 that is, athletes who would be considered "unhealthy" perfectionists according to the model in Figure 1-showed the largest performance increments over a series of trials .…”
Section: Sport Performance [H2]mentioning
confidence: 99%
“…Speculating on why this was the case, Stoll et al (2008) noted that the scale they used to measure perfectionistic concerns (the MIPS Negative Reactions to Imperfection scale) contains items that J. Stoeber: Perfectionism and Performance 14 capture anger, dissatisfaction, and frustration after mistakes and unsatisfactory performance (e.g., "I get completely furious when I make a mistake"). Thus athletes who were high in both dimensions of perfectionism-high in perfectionistic strivings and high in negative reactions to imperfection-may have wanted to show a perfect training performance, but experienced more anger, frustration, and dissatisfaction with their imperfect performance.…”
Section: Sport Performance [H2]mentioning
confidence: 99%
“…Algunos investigadores han argumentado que el perfeccionismo en el deporte es poco adaptativo porque perjudica el rendimiento (Flett & Hewitt, 2005); mientras que otros investigadores ven el perfeccionismo como un rasgo adaptativo que ayuda a la obtención de un buen rendimiento (Gould, Dieffenbach, & Moffett, 2002), y a aprender nuevas habilidades deportivas (Stoll, Lau, & Stoeber, 2008).…”
Section: Introductionunclassified
“…Numerous researchers have explored the attributes and skills that differentiate elite and sub-elite athletes, including technical ability (Coelho e Silva et al, 2010;Figueiredo et al, 2009;le Moal et al, 2013), physical fitness (Deprez, Fransen, Boone, Lenoir, Philippaerts, & Vaeyens, 2015;le Gall, Carling, Williams & Reilly, 2010), personality characteristics (Guelmami, Hamrouni, & Agrébi, 2014;Reilly, Williams, Nevill, & Franks, 2000;Stoll, Lau, & Stoeber, 2008), and perceptualcognitive expertise (Farrow, McCrae, Gross, & Abernethy, 2010;Larkin, Berry, Dawson, & Lay, 2011;Larkin, Mesagno, Berry, & Spittle, 2014;Roca, Williams, & Ford, 2012). Moreover, researchers have investigated the practice history profiles of elite athletes to better understand what activities may contribute to the development of elite level performance (Ford, Ward, Hodges, & Williams, 2009;Ward, Hodges, Starkes, & Williams, 2007; Williams, Ward, Bell-Walker & Ford, 2012).…”
mentioning
confidence: 99%